Sistem Monitoring PH Pada Tanaman Kelapa Sawit Berbasis IoT - M Yusuf Nurul Yakin; Jefri Lianda; Adam Adam (Universitas Pahlawan Tuanku Tambusai, 2026)
This study presents the design of a soil pH monitoring system for oil palm plants integrated with Internet of Things (IoT) technology for real-time monitoring of soil conditions. The system consists of a soil pH sensor, a NodeMCU ESP8266 microcontroller, and a monitoring platform for data visualization. Testing was conducted on several soil samples to evaluate the performance of the system in measuring and transmitting pH data. The results show that the system is capable of monitoring soil pH accurately and continuously in real time. The monitoring platform successfully displays pH data, allowing users to observe soil conditions remotely and efficiently. The results indicate that the proposed system works effectively and can support better soil management practices for oil palm cultivation.